(untitled) (Research, Society and Development, 2025)
Obesity is characterized as a chronic, multifactorial disease, with a prevalence observed on a global scale, affecting individuals of any age, sex, gender, or social class. In addition to impacting quality of life, obesity negatively affects systemic health and is associated with various comorbidities, such as insulin resistance, cardiovascular alterations, and respiratory disorders. Systemic inflammation resulting from obesity can also affect oral health, influencing the development and progression of periodontal disease. In this context, recent studies indicate an association between obesity and periodontal disease. Therefore, this study aims to highlight, through a literature review, the relationship between obesity and periodontal disease. This is an exploratory bibliographic research that seeks to analyze the knowledge available in the literature regarding this association. Data collection was conducted through a systematic search of scientific articles in the PubMed, SciELO, and Google Scholar databases. The results demonstrate that obesity acts as an active agent in the inflammatory modulation of the body. Adipose tissue, particularly white adipose tissue, excessively secretes pro-inflammatory cytokines capable of causing significant changes in periodontal tissues; consequently, obese patients show a higher predisposition to elevated periodontal disease parameters. It is concluded, therefore, that obesity constitutes a significant risk factor for the development and progression of periodontal disease, as well as its high prevalence in obese individuals, reinforcing the need for integrated prevention and therapeutic strategies. Thus, the involvement of the dentist in the multiprofessional care of obese patients becomes essential.